Thomas & friends. Thomas' Christmas carol [videorecording (DVD)] - Allcroft, Britt (Universal Studios Home Entertainment, 2015)
It's a winter wonderland on Sodor! Diesel gets a visit from some 'ghostly' Christmas engines, while Kevin enjoys playing in the snow until he's snowed under. Thomas and Cranky drop an important Christmas package and Henry faces off against an abominable snowman. Dash through the snow with Thomas and his friends as they deliver a jolly good time!